Effect of pulsatile and nonpulsatile flow on cerebral perfusion in patients with left ventricular assist devices - Cornwell, William K.; Tarumi, Takashi; Aengevaeren, Vincent L.; Ayers, Colby; Divanji, Punag; Fu, Qi; Palmer, Dean; Drazner, Mark H.; Meyer, Dan M.; Bethea, Brian T.; Hastings, Jeffrey L.; Fujimoto, Naoki; et al. (The Journal of heart and lung transplantation, 2014)
Insertion of a left ventricular assist device (LVAD) is an accepted therapy for advanced heart failure patients. However, the effects on end-organ perfusion, including cerebral autoregulation, are unclear in the presence of reduced pulsatility. Therefore, the objective of this study was to determine whether cerebral autoregulation is impaired in patients with continuous-flow (CF) LVADs. Dynamic cerebral autoregulation was assessed in both time-domain (autoregulatory index) and frequency-domain (transfer function analysis) analyses in 9 CF-LVAD subjects, 5 pulsatile LVAD subjects and 10 healthy controls, by evaluating mean arterial pressure (MAP) and cerebral blood flow velocity (CBFV) during a sit–stand maneuver at 0.05 Hz (10-second sit, 10-second stand). The autoregulatory index was calculated as the percent change in mean CBFV per mm Hg change in MAP. The magnitude of oscillation in MAP and CBFV was greater in subjects with pulsatile LVADs than either CF-LVADs or healthy controls (p = 0.065 for MAP, p = 0.004 for CBFV). The autoregulatory index and transfer function gain were similar among groups, indicating that dynamic cerebral autoregulation is preserved among patients with CF-LVADs. Cerebral blood flow in patients with CF-LVADs is comparable to that of healthy controls across a range of blood pressures. Patients with pulsatile devices have greater oscillations in MAP and CBFV. However, dynamic cerebral autoregulation is preserved among subjects with either type of device. Thus, the reduction in pulsatility afforded by CF-LVADs does not impair normal autoregulatory processes.